2009
DOI: 10.1007/s11199-009-9620-x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Overprotection, Cultural Value Conflict, and Psychological Adaptation among Asian Indian Women in America

Abstract: The present study related generational status, marital status, parental overprotection (control), and cultural value conflict to self-esteem and depression among first and second-generation Asian Indian immigrant women in the south-midwestern United States. Self-report data from 73 community-dwelling women supported the hypotheses that unmarried and second-generation women would report greater maternal control and cultural value conflict than would married and first-generation women. Secondgenerational status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 32 publications
(47 reference statements)
3
34
0
Order By: Relevance
“…Among female immigrants, those in the lower socioeconomic strata had the lowest incidence rate ratios for both adverse outcomes, and the female effect sizes rose in incremental fashion across the socioeconomic strata. This pattern could perhaps be explained by lower socioeconomic status female immigrants, especially those originating from non-western countries, being strongly protected by their parents and other close family members from social stressors and from peers experiencing psychosocial difficulties, right up until the age when they marry [ 66 ]. Such close social control and protection may be less likely to occur among young immigrant females in the middle and higher socioeconomic strata.…”
Section: Discussionmentioning
confidence: 99%
“…Among female immigrants, those in the lower socioeconomic strata had the lowest incidence rate ratios for both adverse outcomes, and the female effect sizes rose in incremental fashion across the socioeconomic strata. This pattern could perhaps be explained by lower socioeconomic status female immigrants, especially those originating from non-western countries, being strongly protected by their parents and other close family members from social stressors and from peers experiencing psychosocial difficulties, right up until the age when they marry [ 66 ]. Such close social control and protection may be less likely to occur among young immigrant females in the middle and higher socioeconomic strata.…”
Section: Discussionmentioning
confidence: 99%
“…Asian Indian individuals were our reference group. We also entered two more dummy variables to control for the effects of gender and immigration status, because of differences reported in prior research among South Asian American individuals related to gender (Alam, 2013; Alam, 2014; Khuwaja et al, 2012; Varghese & Jenkins, 2009) and immigration and acculturative experiences (Alam, 2013; Alam, 2014; Farver et al, 2002; Khuwaja et al, 2012; Patel & Gaw, 1996; Varghese & Jenkins, 2009). Brooding and reflective rumination, as measured by the Ruminative Response Scale (Nolen-Hoeksema & Morrow, 1991), were also originally included in our model as predictors, both separately and in interaction terms with the previously noted ethnic status dummy variables, to explore their effects on suicidal ideation.…”
Section: Methodsmentioning
confidence: 99%
“…One study reported that the breadth of the acculturative gap between Asian Indian adolescents and their parents was negatively related to self-esteem and positively related to anxiety and family conflict (Farver, Narang, & Bhadha, 2002). Another study found that second-generation unmarried Asian Indian women reported greater maternal control and cultural value conflict than first generation or married peers, and that this conflict mediated a relation between perceptions of maternal control and depressive symptoms (Varghese & Jenkins, 2009). Such cultural value conflict may arise from divergent expectations about sex roles, such as the expectation that one should eschew dating before parentally arranged marriage (Varghese & Jenkins, 2009).…”
Section: Characteristics Of South Asian American Groupsmentioning
confidence: 99%
“…A.K emphasises the 'shame' value and how honour can be violated as a result of technology misuse, while S.Y discusses how children are becoming less active due to technology. Interestingly, S.Y follows up by referring to how he was not idle at a young age, which allowed him to do 'paper rounds' thus emphasising the economic responsibility which is often associated with South Asian males (Varghese and Jenkins 2009). Thus, the degree to which parents see the risks of technology are magnified as a result of their collectivist value systems, which are deep-rooted as evident, even in second and third generation South Asians.…”
Section: 'Izzet' Takes Lifetime To Build Few Clicks To Destroy' -Magmentioning
confidence: 99%